A new PGPR co-inoculated with Bradyrhizobium japonicum enhances soybean nodulation - Masciarelli, Oscar Alberto (2014)
A new PGPR (plant growth promoting rhizobacteria) strain was isolated from soybean seeds and the bacterial mechanisms related to plant growth promotion were evaluated and characterized. Isolates were genotypically compared and identified by amplification of partial sequences of 16S DNAr as Bacillus amyloliquefaciens strain LL2012. Isolates were grown until exponential growth phase to evaluate the atmospheric nitrogen fixation, enzymatic activities, phosphate solubilization, siderophores and phytohormones production. LL2012 strain was able to grow and to produce high levels of auxin, gibberellins and salicylic acid in chemically defined medium. Co-inoculation of soybean plants with LL2012 strain and the natural symbiont (Bradyrhizobium japonicum) altered plant growth parameters and significantly improved nodulation. Our results show that the association of LL2012 with B. japonicum, enhanced the capacity of the latter to colonize plant roots and increase the number of nodules, which make the co-inoculation technique attractive for use in commercial inoculant formulations following proper field evaluation.